Rosiglitazone-enriched diet did not protect liver ischemia-reperfusion injury in a rat model - Teixeira,Antonio Roberto Franchi (2008)
PURPOSE: To determine whether rosiglitazone-enriched diet offer protection in a classical model of liver ischemia-reperfusion injury in rats. METHODS: Two days before the experiment, rats were divided into 2 groups: Control Group (n=13) rats fed with standard diet; Rosi Group (n=13): rats fed with a powdered standard diet supplemented with rosiglitazone. The animals were submitted to liver ischemia-reperfusion by clamping the pedicle of median and left anterolateral lobes. After 1 hour of partial hepatic ischemia, the clamp was removed for reperfusion. After 2 or 24 hours (Control and Rosi Groups), blood was collected for enzymes and cytokines analysis. Ischemic and non-ischemic liver were collected for malondialdehyde analysis and histological assessment. Lungs were removed for tissue myeloperoxidase quantification. RESULTS: There were no statistical differences between groups for all analysed parameters. CONCLUSION: In this model, rosiglitazone-enriched diet did not protect liver against ischemia-reperfusion injury.